Strategies to overcome CAR-T cell resistance in clinical work: A single-institute experience - Nan, Feifei; Fu, Xiaorui; Chen, Xinfeng; Li, Ling; Li, Xin; Wu, Jingjing; Feng, Xiaoyan; Wu, Xiaolong; Yan, Jiaqin; Zhang, Mingzhi (Frontiers in Immunology, 2022)
The emergence of chimeric antigen receptor (CAR) T-cell therapy has shifted the paradigm of malignant tumor treatment, especially the advent of CD19-directed CAR-T-cell therapy for the treatment of relapsed/refractory (R/R) B-cell malignancies. Although CAR-T-cell therapy has promising effects, some patients are resistant to this treatment, leaving them with limited options. Therefore, strategies to overcome resistance to CAR-T-cell therapy are needed. We retrospectively studied three R/R diffuse large B-cell lymphoma (DLBCL) patients who were resistant to CAR-T-cell therapy and whose disease was controlled after receiving pembrolizumab, 21D4 CAR-T cells, or ibrutinib and venetoclax. Some promising prevention and treatment strategies to overcome treatment resistance are also discussed.